Analisis Pengetahuan Ibu Nifas Tentang Posisi Menyusui Yang Benar Di Puskesmas Pattallassang - Sumaifa Sumaifa; Risnawati Risnawati (STIKes Ibnu Sina Ajibarang, 2023)
The puerperium is a period of recovery, starting from completion of labor until the obstetrical devices such as pre-pregnancy, the length of the puerperium is 6-8 weeks. Breastfeeding is a skill that is learned by both mother and baby, both of which require time and patience to fulfill nutrition in infants for 6 months. Knowledge is one of the influencing factors, the formation of a person's attitude. Based on experience and research, if a person has good nowledge then he will also have good behavior. Based on this thought, a study is needed that aims to find out the Knowledge Analysis of Postpartum Mothers Regarding Correct Breastfeeding Positions at the Pattallassang Health Center in 2023. The type of research used is a quantitative descriptive research method, namely researchers will only describe certain variables and are presented in a frequency distribution table. Sampling of this study using total sampling technique, namely the technique of determining the sample when all members of the population are used as samples, the sample size is 26 people with the Frequency Distribution formula. The results showed that the mother's knowledge of the correct breastfeeding position, that is, of the 26 mothers in the study, the frequency of mothers who had good knowledge of the correct breastfeeding position was 6 people (23.0%). Counseling was increased effectively and continuously regarding equipped with media counseling in the form of posters and advertisements and always continuing education and increasing knowledge so that they can be more skilled in providing health services to clients.